2011
DOI: 10.1111/j.1439-0485.2011.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental gradients on sandy beach macrofauna of a semi‐enclosed bay

Abstract: Macrofauna of sheltered and pocket beaches located in embayments, estuaries or landward of protective reefs has not been adequately assessed in beach ecology. In this setting, the concurrent role of large‐scale morphodynamics and wave‐exposure gradients in shaping biological patterns is still uncertain. To examine variations in community descriptors and the influence of physical factors on macrofauna, 12 sandy beaches on five islands within Sepetiba Bay (SE Brazil) were characterized in terms of beach morphody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…Because of the species' high abundance, the production of A. brasiliana accounts for a high percentage of the overall production of the local macrofaunal community. Among mollusks, A. brasiliana and the gastropod Cerithium atratum comprise more than 80% of all individuals in the macrofaunal community (Cardoso et al 2011). On the other hand, the P/B ratio calculated for D. punctata was higher than for A. brasiliana, a difference which possibly relates to the former species' lower individual body mass (Brey and Clarke 1993;Tumbiolo and Downing 1994) and longevity (Waters 1977;Robertson 1979).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Because of the species' high abundance, the production of A. brasiliana accounts for a high percentage of the overall production of the local macrofaunal community. Among mollusks, A. brasiliana and the gastropod Cerithium atratum comprise more than 80% of all individuals in the macrofaunal community (Cardoso et al 2011). On the other hand, the P/B ratio calculated for D. punctata was higher than for A. brasiliana, a difference which possibly relates to the former species' lower individual body mass (Brey and Clarke 1993;Tumbiolo and Downing 1994) and longevity (Waters 1977;Robertson 1979).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have focused on community ecology and population dynamics of macrofauna from exposed beaches McLachlan 2005, 2011), while sheltered beaches have been a historically neglected area of sandy-beach ecology (Cardoso et al 2011). Surprisingly, few studies have analyzed population parameters of sheltered beach macrofauna (Denadai et al 2004;Abrahão et al 2010), even though these environments support a high diversity of species (Dexter 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At its western end, the Sepetiba Bay is connected to Ilha Grande Bay by a narrow channel in which the main current direction is from west to east (Signorini 1980, Fragoso 1999. Cardoso et al (2012), studying 12 sandy beaches on five islands within Sepetiba Bay, showed that the species richness and total abundance markedly increase in the inner bay, where the wave action is minimal. They also verified that wave exposure variability, sediment variables (e.g.…”
Section: Study Areamentioning
confidence: 99%
“…Based on the environmental characteristics, the bay can be divided into three sectors: the inner sector (influenced by freshwater discharges from several small rivers), the outer sector (influenced by oceanic waters and in contact with the Atlantic Ocean by a wide mouth located at its western end) and the middle sector (a mixed zone with intermediate environmental conditions influenced by freshwater discharges and by oceanic waters). The outer sector is marked by the presence of islands with several sheltered and exposed sandy beaches (Cardoso et al 2012). The mean tidal range of the region is 1.50 m and currents, with a maximum speed of approximately 1 m/s, mainly regulate the hydrodynamic conditions (Fragoso 1999).…”
Section: Study Areamentioning
confidence: 99%